2011
DOI: 10.1007/s10995-011-0914-6
|View full text |Cite
|
Sign up to set email alerts
|

Racial/Ethnic Disparities in Maternal Morbidities: A Statewide Study of Labor and Delivery Hospitalizations in Wisconsin

Abstract: We examined racial/ethnic disparities in maternal morbidities (MM) and the number of MM during labor and delivery among hospital discharges in Wisconsin. We conducted a retrospective cohort study of hospital discharge data for 206,428 pregnant women aged 13-53 years using 2005-2007 Healthcare Cost and Utilization Project State Inpatient Dataset (HCUP-SID) for Wisconsin. After adjustments for covariates, MM (preterm labor, antepartum and postpartum hemorrhage, hypertension in pregnancy, gestational diabetes, me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
48
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(53 citation statements)
references
References 68 publications
3
48
2
Order By: Relevance
“…Still others suggested the primary cause of the racially based differences in clinical outcomes arises from connective tissue differences. Previous studies have shown that African American women are protected [8,12,13] from developing severe lacerations, and our data corroborate these findings.…”
Section: Discussionsupporting
confidence: 91%
“…Still others suggested the primary cause of the racially based differences in clinical outcomes arises from connective tissue differences. Previous studies have shown that African American women are protected [8,12,13] from developing severe lacerations, and our data corroborate these findings.…”
Section: Discussionsupporting
confidence: 91%
“…Similar findings were made in a large Wisconsin study recruited from hospital discharge data. AA women had the highest risk for all the different types of preeclampsia when compared with European American women 27 . Several other studies looking at risk factors for both eclampsia and preeclampsia in nulliparous and parous women have also shown AA are at higher risk (Table 2).…”
Section: Preeclampsia Among African Americansmentioning
confidence: 83%
“…The role of race is of interest given considerable racial disparities in risk for adverse birth outcomes; in the US, Black women show 1.3 to 1.5-fold higher risk than Whites for adverse outcomes including gestational hypertension and preterm birth (Hamilton et al 2015, Ghosh et al 2014, Cabacungan, Ngui & McGinley 2012). These outcomes have been linked with dysregulation of inflammatory processes (Kuklina, Ayala & Callaghan 2009, Reddy et al 2015, Behrman, Stith Butler 2007, Mendola et al 2015, Hamilton et al 2015).…”
Section: Introductionmentioning
confidence: 99%